PENERAPAN METODE INQUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 018 BAGAN HULU - Antosa, Zariul Antosa Zariul; Daud, Damanhuri Daud Damanhur; ', Rini Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:Problems in the Classroom Action Research This is how the application of inquiry methods to improve student learning outcomes IPS Public Elementary School fourth grade 018 Chart Hulu. It is necessary for improvement in order to improve learning outcomes. Improvement efforts carried out by applying the method of inquiry. The research was conducted in the fourth grade 018 State Primary School Academic Year 2013/2014 Chart Hulu with a research conducted on April 9, 2013-2 May 2013 subjects were fourth graders State Primary School Upper 018 Chart with the number of students 27 people, who consisted of 15 male students and 12 female students. Data collection techniques used were observation and testing techniques. Data analysis techniques used namely learning outcomes, individual completeness and classical, teacher and student activities, individual awards. The results showed that the initial data is known that the IPS student learning outcomes of students in average only 60.2 and completeness of 22.2% were achieved with less category. In the first cycle of the first meeting of the class action and evacuated after there was a slight increase student learning outcomes IPS averaging 63.9 and classical completeness still reached 40.7% or less still in the category. In the first cycle of the second meeting of the IPS student learning outcomes are to increase the average -rata achieved by 67.9 and 59.3% for classical completeness. Seeing conditions achieved in the first cycle of meetings 1 and 2, the researchers took the initiative to continue kep siklsu II. After learning social studies carried out in this second cycle of learning outcomes achieved by students at the first meeting that reached an average of 69.2 and 66.6% for classical completeness and in the second meeting there is a very significant increase in the average reached 80.7 and classical completeness amounted to 96.3% with the excellent category. This means that the inquiry method of learning is one of the effective methods to improve learning outcomes IPS Elementary School fourth grade students 018 Bagan Hulu. Keyword: Inkuiri, The result of social studies